Optimasi Rute Distribusi Spare Part Motor Menggunakan Ant Colony Optimization untuk Efisiensi Jarak Tempuh - Nani Agustina; Entin Sutinah; Martini Martini (Journal of Information System Research (JOSH), 2026)
Logistics efficiency in goods distribution has become a major challenge for distribution companies in reducing operational costs. This study aims to optimize the distribution routes of motorcycle spare parts at PD. Tri Jaya Motor using the Ant Colony Optimization (ACO) algorithm. The main issue faced by the company is the use of unsystematic manual route determination, which results in inefficient travel distances. The methodology employed in this research involves modeling the Traveling Salesman Problem (TSP) across six distribution points using parameters of alpha = 1, beta = 1, and rho = 0.1. The simulation results demonstrate that the ACO algorithm successfully identified the optimal route with a total distance of 206.6 km, resulting in significant savings compared to the initial route. This study contributes by providing a metaheuristic-based decision-making strategy for medium-scale distribution systems.